2018
DOI: 10.1038/s41396-017-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of niche and physiological differentiation of archaeal and bacterial ammonia oxidisers for nitrous oxide emissions

Abstract: High and low rates of ammonium supply are believed to favour ammonia-oxidising bacteria (AOB) and archaea (AOA), respectively. Although their contrasting affinities for ammonium are suggested to account for these differences, the influence of ammonia concentration on AOA and AOB has not been tested under environmental conditions. In addition, while both AOB and AOA contribute to nitrous oxide (N2O) emissions from soil, N2O yields (N2O–N produced per NO2−–N generated from ammonia oxidation) of AOA are lower, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
158
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(195 citation statements)
references
References 67 publications
25
158
1
Order By: Relevance
“…In contrast, AOA produce lower amounts of N 2 O, which is mainly generated by abiotic reactions from ammonia oxidation intermediates (Kozlowski et al 2016b; Stieglmeier et al 2014). In agreement with these data from pure culture studies, mesocosm experiments revealed an increased N 2 O yield in fertilized soil when ammonia oxidation was dominated by AOB (Hink et al 2018). In AOB, enzymatic N 2 O production is catalyzed by nitric oxide reductases (NOR) that convert NO derived from nitrite reduction (Kozlowski et al 2016a), and cytochrome P460, a periplasmic metalloenzyme shown to directly convert NH 2 OH to N 2 O under anaerobic conditions (Caranto et al 2016).…”
Section: Potential Niche-defining Differences Between Strict Ammonia supporting
confidence: 74%
“…In contrast, AOA produce lower amounts of N 2 O, which is mainly generated by abiotic reactions from ammonia oxidation intermediates (Kozlowski et al 2016b; Stieglmeier et al 2014). In agreement with these data from pure culture studies, mesocosm experiments revealed an increased N 2 O yield in fertilized soil when ammonia oxidation was dominated by AOB (Hink et al 2018). In AOB, enzymatic N 2 O production is catalyzed by nitric oxide reductases (NOR) that convert NO derived from nitrite reduction (Kozlowski et al 2016a), and cytochrome P460, a periplasmic metalloenzyme shown to directly convert NH 2 OH to N 2 O under anaerobic conditions (Caranto et al 2016).…”
Section: Potential Niche-defining Differences Between Strict Ammonia supporting
confidence: 74%
“…However, several studies have demonstrated that amoA gene abundance derived from qPCR varies in response to factors that also affect nitrification rates (Carey et al 2016). Several lines of Lu et al 2015, Hink et al 2018, as was the case in our study system. However, our study system differs from most of the studies included in the Carey et al (2016) metaanalysis in two fundamental ways.…”
Section: Contrasting Differences In Aoa and Aob Responsessupporting
confidence: 52%
“…This knowledge gap exists in part because, within the last decade, evidence has accumulated for a previously unknown, large, and nearly ubiquitous group of soil ammonia oxidizers in the domain Archaea (Francis et al 2005, Nicol and. More recent studies indicate that ammonia-oxidizing archaea (AOA) in the Thaumarchaeota outnumber ammonia-oxidizing bacteria (AOB) in most soils (Leininger et al 2006, Adair andSchwartz 2008), and that AOA may dominate over AOB in controlling nitrification rates in terrestrial ecosystems with low-to-moderate N availability (Carey et al 2016, Hink et al 2018). More recent studies indicate that ammonia-oxidizing archaea (AOA) in the Thaumarchaeota outnumber ammonia-oxidizing bacteria (AOB) in most soils (Leininger et al 2006, Adair andSchwartz 2008), and that AOA may dominate over AOB in controlling nitrification rates in terrestrial ecosystems with low-to-moderate N availability (Carey et al 2016, Hink et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…AOB growth is favored in soils fertilized by single additions of high levels of inorganic NH 3 , while AOA grow preferentially when NH 3 is produced through mineralization of organic N (Hink, Gubry-Rangin, Nicol, & Prosser, 2018;Verhamme, Prosser, & Nicol, 2011). AOB growth is favored in soils fertilized by single additions of high levels of inorganic NH 3 , while AOA grow preferentially when NH 3 is produced through mineralization of organic N (Hink, Gubry-Rangin, Nicol, & Prosser, 2018;Verhamme, Prosser, & Nicol, 2011).…”
Section: Ni Che S Pecializ Ati On and Differentiation In Ammonia Oxmentioning
confidence: 99%
“…To test the potential for reduction in N 2 O through use of different fertilizer strategies, a similar approach compared single addition of urea-N at high concentration and continuous low production from a slow-release urea-N fertilizer (polymethylene urea) or organic N mineralization (Hink et al, 2018). AOA-associated N 2 O emission was also determined in unfertilized soils, in which NH 3 is supplied through mineralization of organic N, and N 2 O yields were again similar to those reported for AOA cultures.…”
Section: Terre S Trial Ecosys Temsmentioning
confidence: 99%